RETRACTED: Assessment of hydraulic friction in polypropylene pipes - Arifjanov Aybek; Atakulov Dinislom; Parpiyev Sayfiddin; Ibragimova Zaytuna; Makhmudov Bekzod (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001